Bioaugmentation for improving the activated sludge process of treating refinery spent caustic: laboratory and field pilot-scale studies. Issue 47 (7th October 2016) - Sun, Shanshan; Fang, Li; Song, Zhaozheng; Wang, Xiaojun; Wang, Jingxiu; Luo, Yijing; Zhang, Zhiyong; Zhang, Guangqing; Jiang, Qingzhe; Zhang, Zhongzhi
Abstract: In this work, successful treatment of refinery spent-sulfidic caustic was achieved in activated sludge system bioaugmented with three specific bacterial strains (including Bacillus thuringiensis, Bacillus cereus, and Acidovorax ebreus ) at both laboratory and pilot scale. After 18-fold dilution by volume, the diluted wastewater was treated aerobically. The volumetric loading rate of chemical oxygen demand (COD) was studied by treating variously diluted samples of high-strength wastewater (COD 3, 100–3, 600 mg/L). The results obtained with the raw wastewater were remarkably good, with an average COD removal of around 80%. The addition of peptone and trace elements improved the performance of the process. The mixed liquor suspended solids (MLSS) concentration in the reactors could be increased from the 2, 500–3, 000 mg/L MLSS level of general activated sludge processes to 6, 000–8, 000 mg/L after installation of draft tubes. These results showed that activated sludge process may be a powerful tool for treating refinery spent caustic by bioaugmentation and nutrient amendment.